Perspectives on a Materialist Ecosemiotics. Coexisting with Other Life and Non-life Forms - Zengiaro , Nicola (E|C, 2024)
The article introduces the field of ecosemiotics, outlining its genealogy and perspectives in relation to ecology, biosemiotics, and cultural semiotics. The paper is structured into three sections: the first section examines the evolution of ecology towards a qualitative and complex investigation of ecosystems and environmental relationships, highlighting the efficacy of semiotic methodology in analyzing ecosystems and the living systems that shape them. The second section provides a brief genealogy of ecosemiotics, distinguishing it from, and drawing parallels with, biosemiotics and cultural semiotics. The third section presents a critique of contemporary ecosemiotics, proposing a materialist approach to analyze the role of both living and non-living entities in the formation of complex ecosystems. The aim of this article is to bring the ecosemiotic debate into the Italian context while demonstrating the value of this perspective in addressing the challenges posed by the current climate and ecological crisis. It seeks to reinterpret non-human semiosis to foster coexistence in increasingly complex environments shaped by the ongoing crisis of the Anthropocene.